Using Autoantibodies and Cutaneous Subset to Develop Outcome‐Based Disease Classification in Systemic Sclerosis - Nihtyanova, Svetlana I.; Sari, Alper; Harvey, Jennifer C.; Leslie, Anna; Derrett‐Smith, Emma C.; Fonseca, Carmen; Ong, Voon H.; Denton, Christopher P. (Arthritis & rheumatology (Hoboken, N.J.), 2020)
Objective To describe the associations between autoantibodies, clinical presentation, and outcomes among patients with systemic sclerosis (SSc) in order to develop a novel SSc classification scheme that would incorporate both antibodies and the cutaneous disease subset as criteria. Methods Demographic and clinical characteristics, including cutaneous subset, time of disease and organ complication onset, and autoantibody specificities, were determined in a cohort of SSc subjects. Survival analysis was used to assess the effect of the autoantibodies on organ disease and death. Results The study included 1,325 subjects. Among the antibody/skin disease subsets, anticentromere antibody–positive patients with limited cutaneous SSc (lcSSc) (n = 374) had the highest 20‐year survival (65.3%), lowest incidence of clinically significant pulmonary fibrosis (PF) (8.5%) and scleroderma renal crisis (SRC) (0.3%), and lowest incidence of cardiac SSc (4.9%), whereas the frequency of pulmonary hypertension (PH) was similar to the mean value in the SSc cohort overall. The anti–Scl‐70+ groups of patients with lcSSc (n = 138) and patients with diffuse cutaneous SSc (dcSSc) (n = 149) had the highest incidence of clinically significant PF (86.1% and 84%, respectively, at 15 years). Anti‐Scl‐70+ patients with dcSSc had the lowest survival (32.4%) and the second highest incidence of cardiac SSc (12.9%) at 20 years. In contrast, in anti‐Scl‐70+ patients with lcSSc, other complications were rare, and these patients demonstrated the lowest incidence of PH (6.9%) and second highest survival (61.8%) at 20 years. Anti–RNA polymerase antibody–positive SSc patients (n = 147) had the highest incidence of SRC (28.1%) at 20 years. The anti–U3 RNP+ SSc group (n = 56) had the highest incidence of PH (33.8%) and cardiac SSc (13.2%) at 20 years. Among lcSSc patients with other autoantibodies (n = 295), the risk of SRC and cardiac SSc was low at 20 years (2.7% and 2.4%, respectively), while the frequencies of other outcomes were similar to the mean values in the full SSc cohort. Patients with dcSSc who were positive for other autoantibodies (n = 166) had a poor prognosis, demonstrating the second lowest survival (33.6%) and frequent organ complications. Conclusion These findings highlight the importance of autoantibodies, cutaneous subset, and disease duration when assessing morbidity and mortality in patients with SSc. Our novel classification scheme may improve disease monitoring and benefit future clinical trial designs in SSc.